Join IDNLearn.com today and start getting the answers you've been searching for. Discover in-depth and reliable answers to all your questions from our knowledgeable community members who are always ready to assist.

(x - 2)(x + 1) = 3x - 2

Sagot :

Answer:

x=4

Step-by-step explanation:

(x-2)(x+1)=3x-2

x(x+1)-2(x+1)=3x-2

x^2+x-2x-2=3x-2

x^2-x-2=3x-2

x^2=3x+x-2+2

x^2=4x

x^2/x=4

x=4

(x - 2) ( x + 1) = 3x - 2

x² + x - 2x - 2 = 3x - 2

x² + x - 2x - 2 - 3x + 2 = 0

x² - 4x = 0

x ( x - 4 ) = 0

x - 4 = 0/x

x - 4 = 0

x = 4